The Influence Of Self-Confidence And Courage To Take Risks On The Performance Of Micro, Small, And Medium Culinary Businesses In Bengkulu City - Hijeria, Putri; Anzori, Anzori; Tambunan, Dennis Rydarto (Universitas Dehasen Bengkulu, 2025)
This study is motivated by the low level of self-confidence and the lack of courage to take risks among culinary MSME (Micro, Small, and Medium Enterprises) entrepreneurs in Bengkulu City, which has resulted in suboptimal business performance. The purpose of this study is to determine the effect of self-confidence and risk-taking courage on the performance of culinary MSMEs, both partially and simultaneously. This research uses a quantitative approach with an associative type of study. Data were collected from 99 respondents through a Google Form–based questionnaire. The research instrument was designed using a five-point Likert scale, while data analysis was carried out using multiple linear regression with the assistance of SPSS version 27.The results show that self-confidence (X1) has a positive and significant effect on MSME performance (Y), with a t-value of 2.640 > t-table 1.985 and a significance value of 0.010 < 0.05. Risk-taking courage (X2) also has a positive and significant effect, with a t-value of 3.503 > 1.985 and a significance value of 0.001 < 0.05. Simultaneously, both variables significantly affect performance, as indicated by an F-value of 22.414 > F-table 3.09 with a significance level of 0.000. The coefficient of determination (R2) value of 0.318 indicates that 31.8% of the variation in MSME performance is influenced by these two variables, while the remaining 68.2% is explained by other factors.